Should I stay or should I go? Migration and job-skills mismatch among Italian doctoral recipients - Vincenzo Alfano; Marcella D'Uva; Elina De Simone; Giuseppe Lucio Gaeta (Global Labor Organization (GLO), 2019)
Finding a non-academic job in line with both doctoral graduates' degree and acquired know-how can be difficult because of insufficient demand for R&D skills in public administration and private enterprise and/or because of the lack of matching between the existing demand and the Ph.D. holders' specialization. The aim of this paper is to test whether migrating from some regions may improve job-education matching in Italy. The econometric strategy takes into account Ph.D. holders' selfselection into non-academic employment as well as the endogeneity of the migration choice. Results demonstrate that migration seems to facilitate the possibility of finding better job opportunities. More specifically, only migration within the regions of the centre and north of Italy seems to improve jobeducation matching.
Keywords: J61; J24; 330; Ph.D. holders; job-education mismatch; migration